Features of Monostotic Fibrous Dysplasia in Maxilla using Cone Beam Computed Tomography - Pillai, Devika S.; Babu, G. Subhas; Hegde, Shruthi; Ajila, Vidya; Ram, Sachin (European Journal of Therapeutics, 2023)
Fibrous dysplasia (FD) is a benign nonneoplastic bone disorder in which fibrous tissue replaces normal bone. It is a genetic non-inherited condition caused by a mutation in the GNAS1 gene and is characterized by abnormal proliferation of fibrous tissue interspersed with normal or immature bone. FD causes esthetic disfigurement and loss of function when the maxillo-mandibular region is affected. A dental practitioner can be the first to detect such conditions. We reported a case of a 28-year-old male, with a history of swelling of the left side of the maxilla for 20 years. The present report highlights the clinical, radiographic, and histopathologic features of this condition along with a review of past literature.